2021
DOI: 10.3389/ffgc.2021.626635
|View full text |Cite
|
Sign up to set email alerts
|

Where Might We Find Ecologically Intact Communities?

Abstract: Conservation efforts should target the few remaining areas of the world that represent outstanding examples of ecological integrity and aim to restore ecological integrity to a much broader area of the world with intact habitat and minimal species loss while this is still possible. There have been many assessments of “intactness” in recent years but most of these use measures of anthropogenic impact at a site, rather than faunal intactness or ecological integrity. This paper makes the first assessment of fauna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 61 publications
1
57
1
Order By: Relevance
“…This "loss of biological diversity is one of the most severe human-caused global environmental problems" [35], particularly with the advent of the 'Great Acceleration'. The short timescale on which these impacts have grown, along with their sheer scope and extent, has resulted in <3% of the world's land surface area remaining as 'fundamentally intact', i.e., with species diversity and habitats unaffected by human activity [36].…”
Section: Ecological Destructionmentioning
confidence: 99%
“…This "loss of biological diversity is one of the most severe human-caused global environmental problems" [35], particularly with the advent of the 'Great Acceleration'. The short timescale on which these impacts have grown, along with their sheer scope and extent, has resulted in <3% of the world's land surface area remaining as 'fundamentally intact', i.e., with species diversity and habitats unaffected by human activity [36].…”
Section: Ecological Destructionmentioning
confidence: 99%
“…This goal is based on the finding that the areas of maximum cultural diversity often overlap with areas of maximum biodiversity [127,128]. The goal should thus be 'to restore ecological integrity to a much broader area of the world with intact habitat and minimal species loss while this is still possible' [129]. Recent research has found that faunally biodiverse areas have rapidly shrunk as a consequence of globalization and state intrusion, so that they are now estimated to cover less than 3% of global land surface [129].…”
Section: Discussionmentioning
confidence: 99%
“…Studying natural ecosystems in light of how they might be negatively impacted by AC as an "external force" implicitly assumes that human activity can be decoupled from natural systems. In the Anthropocene, however, in which few ecosystems on Earth can be considered to be untouched by human agency (Plumptre et al 2021), this assumption may no longer be useful. We must pivot to viewing and understanding neobiota-novel community arrangements and humanaffected ecosystems-as the norm (Ellis et al 2010;Williams et al 2015).…”
Section: Symbiogenesis As a Consequence And Cause Of Anthropogenic Changementioning
confidence: 99%
“…We have no choice but to "face Gaia" (Latour 2017) and understand that we and the effects of our society are inextricably connected with all ecosystems on Earth today. Less than 3% of our Earth's ecosystems remain untouched by human influence (Williams et al 2015;Plumptre et al 2021) and whether we intend to or not, our choices have and will have profound impacts on the future of Earth's biomes, and through reciprocal feedbacks, our own species. The fact that we have agency (and responsibility) should empower us to take a more active role.…”
Section: The Anthropic Biosphere Is a Symbiotic Biospherementioning
confidence: 99%